Religious Trend in Contemporary Indonesia: Conservatism Domination on Social Media - Kirana, Dita; Garadian, Endi Aulia (Studia Islamika, 2020)
Religion is predicted to dissipate from social significance through the processes of development or economic modernization. Classical secularization theory forecasted religion in the modern era will face some circumstances such as 1) the decline of personal faith, religious beliefs and practices; and (2) the retreat of religion from public space (Cassanova: 1994, 2010). However, the supporters of secularization and modernization theories failed to notice that religion did not disappear from the public sphere. The opposite occurs in Southeast Asia. Economic development program and modernization could work hand-in-hand with religion in the region (Feener and Fountain: 2018).In the context of Indonesia, the issue of religion has gone through ups and downs. The story of Indonesia’s revival of Islam had been begun when the country experienced anti-communist campaigns of 1965-66 (McVey: 2006). Since then, the government obliged all of its societies to profess one of Indonesia’s recognized religions: Islam, Catholicism, Protestantism, Buddhism, and Hinduism (now Confucianism has been added to the list) (Qurtuby: 2013). The pressure for all citizens to embrace one particular recognized religion resulted in great conversion from local religions/faiths—Hindu, Buddha, abangan, etc.—to Islam (Hefner: 1987a, 1987b, 1989; cf. Beatty: 1999). It then witnesses rapid growth of the grassroots Islam and the spread of Islamization (Houben: 2003).